Improving Learning Outcomes of Class VB Students in Mathematics Learning Using Scratch Media at SDN 57 Padang Sappa, Luwu Regency: Peningkatan Hasil Belajar Siswa Kelas VB Pada Pembelajaran Matematika Menggunakan Media Scratch di SDN 57 Padang Sappa Kabupaten Luwu - Juwita Crestiani; Aprianti; Sunardin (Journal of Creative Power and Ambition (JCPA), 2026)
Mathematics is one of the important subjects in elementary school (SD). However, many students find it difficult and are not motivated to learn mathematics. This study aims to improve elementary school students' mathematics learning outcomes through Scratch Media. This study uses the Kurt Lewin Classroom Action Method (CAR) model consisting of planning, action, observation, and reflection. It was implemented in two cycles, each cycle carried out in three meetings. The subjects in the study were 25 students, 9 male students and 16 female students. The research instruments were observation sheets for the implementation of learning, observation sheets for student activities and multiple choice tests. The results of the study showed that Scratch Media can improve elementary school students' mathematics learning outcomes. This is evidenced by the results of the first cycle of research showing that the implementation of learning reached 92% in the very good category, student activity reached 86% in the very active category, the average student mathematics learning outcomes reached 74.96 in the good category and classical completeness reached 52%. Indicators of success in this study are found in the second cycle. The results of the study showed an increase seen from the implementation of learning reaching 95% in the very good category, student activity reaching 91% in the very active category, the average student mathematics learning outcomes reaching 89.28 in the very good category and classical completeness reaching 96%. Based on the results of this study, it was concluded that Scratch Media can be an effective alternative to increase the motivation to learn mathematics in elementary school students. The use of Scratch Media in mathematics learning needs to be continuously developed and implemented widely in schools.